2019
DOI: 10.3390/ijerph16234630
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Use Behaviors, and Preferences among Users of Heated Tobacco Products: Findings from the 2018 ITC Japan Survey

Abstract: Heated tobacco products (HTPs), such as IQOS, glo, and Ploom TECH, with a variety of flavored tobacco-containing inserts, have reportedly achieved a significant market share in Japan. We analyzed data from Wave 1 of the ITC Japan Survey, a nationally representative web survey conducted in February to March 2018 among 4684 adult participants to estimate the prevalence of HTP use, describe characteristics of HTP users, and explore user preferences for HTP device and flavor. The overall prevalence of monthly HTP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 31 publications
3
57
1
Order By: Relevance
“…Our study did not examine whether HTP users are former or never-smokers who started using HTPs because they believe they are less harmful alternative to cigarettes, or if current smokers want to substitute their cigarettes with a potentially less harmful alternative; however, some research has suggested that HTPs may in fact be barrier to smoking cessation in Japan. For example, despite PMI's claims that most IQOS users are former smokers [16], independent research has shown that the majority of Japanese HTP users do not quit smoking [29][30][31][32]. For example, Xu et al found that, among the reasons for using HTPs cited by Japanese concurrent users, non-quit reasons-to cut down on cigarettes (64.6%) and to not have to give up cigarettes altogether (52.1%)-were mentioned as often as or more often than the desire to quit smoking (55.4%) [33].…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not examine whether HTP users are former or never-smokers who started using HTPs because they believe they are less harmful alternative to cigarettes, or if current smokers want to substitute their cigarettes with a potentially less harmful alternative; however, some research has suggested that HTPs may in fact be barrier to smoking cessation in Japan. For example, despite PMI's claims that most IQOS users are former smokers [16], independent research has shown that the majority of Japanese HTP users do not quit smoking [29][30][31][32]. For example, Xu et al found that, among the reasons for using HTPs cited by Japanese concurrent users, non-quit reasons-to cut down on cigarettes (64.6%) and to not have to give up cigarettes altogether (52.1%)-were mentioned as often as or more often than the desire to quit smoking (55.4%) [33].…”
Section: Discussionmentioning
confidence: 99%
“…40) 1945 1950 1955 1960 1965 1970 1975 1980 1985 1990 1995 Another Japanese study compared device preference and showed that IQOS was used more by younger people and those who reported daily use. 41) Dunbar et al 42) reported that among young adults in the United…”
Section: Characteristics Of Heated Tobacco Product Usersmentioning
confidence: 99%
“…Exclusive users of HTPs (n = 164) or cigarettes (n = 3194) were defined as participants who only used one of the two products at least once a month, while concurrent cigarette-HTP users (n = 644) reported monthly use of both HTPs and cigarettes. Detailed questions to ascertain participant status to each tobacco product use category have been described elsewhere [7].…”
Section: User Definitionsmentioning
confidence: 99%
“…The popularity of HTPs among affluent population mirrors the price difference between the two products. The price for a pack of cigarettes and a pack of tobacco-containing inserts for HTPs are comparable (In 2018, the price of a pack of cigarettes was approximately ¥500, similarly, the price of a pack of tobacco containing-inserts for IQOS was approximately ¥500) [7]. However, HTP users need to buy the HTP device which cost ranging from 6 to 18 times the price of a pack of cigarettes [7].…”
Section: Characteristics Of Concurrent Cigarette-htp Usersmentioning
confidence: 99%
See 1 more Smart Citation